Islamicate Occult Sciences in Theory and Practice - Saif, Liana,; Leoni, Francesca,; Melvin-Koushki, Matthew,; Yahya, Farouk, (Middle East and Islamic Studies E-Books Online, Collection 2020, ISBN: 9789004405868., 2021)
Islamicate Occult Sciences in Theory and Practice brings together the latest research on Islamic occultism from a variety of disciplinary perspectives, namely intellectual history, manuscript studies and material culture. Its aim is not only to showcase the range of pioneering work that is currently being done in these areas, but also to provide a model for closer interaction amongst the disciplines constituting this burgeoning field of study. Furthermore, the book provides the rare opportunity to bridge the gap on an institutional level by bringing the academic and curatorial spheres into dialogue.